Stillbirths in China: a nationwide survey. (2nd September 2020) - Zhu, J; Zhang, J; Xia, H; Ge, J; Ye, X; Guo, B; Liu, M; Dai, L; Zhang, L; Chen, L; Wang, Y; Wang, X; et al.
Abstract : Objective: To estimate a stillbirth rate at 24 or more gestational weeks in 2015–2016 and to explore potentially preventable causes in China. Design: A multi‐centre cross‐sectional study. Setting: Ninety‐six hospitals distributed in 24 (of 34) provinces in China. Population: A total of 75 132 births at 24 completed weeks of gestation or more. Methods: COX Proportional Hazard Models were performed to examine risk factors for antepartum and intrapartum stillbirths. Population attributable risk percentage was calculated for major risk factors. Correspondence analysis was used to explore region‐specific risk factors for stillbirths. Main outcome measures: Stillbirth rate and risk factors for stillbirth. Results: A total of 75 132 births including 949 stillbirths were used for the final analysis, giving a weighted stillbirth rate of 13.2 per 1000 births (95% CI 7.9–18.5). Small for gestational age (SGA) and pre‐eclampsia/eclampsia increased antepartum stillbirths by 26.2% and 11.7%, respectively. Fetal anomalies increased antepartum and intrapartum stillbirths by 17.9% and 7.4%, respectively. Overall, 31.4% of all stillbirths were potentially preventable. Advanced maternal age, pre‐pregnant obesity, chronic hypertension and diabetes mellitus were important risk factors in East China; low education and SGA were major risk factors in Northwest, Southwest, Northeast and South China; and pre‐eclampsia/eclampsia and intrapartum complications were significant risk factors in Central China. Conclusions: The prevalence of stillbirth was 13.2 per 1000 births in China in 2015–2016. Nearly one‐third of all stillbirths may be preventable. Strategies based on regional characteristics should be considered to reduce further the burden of stillbirths in China. Tweetable abstract: The stillbirth rate was 13.2 per 1000 births in China in 2015–2016 and nearly one‐third of all stillbirths may be preventable. Tweetable abstract: The stillbirth rate was 13.2 per 1000 births in China in 2015–2016 and nearly one‐third of all stillbirths may be preventable.